Pengaruh Influencer Media Sosial dan Testimoni terhadap Minat Beli Produk Erigo di Marketplace Indonesia - Irvan Alfiansya; Nurhadi Nurhadi (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
Currently in Indonesia, the trend of online shopping through the marketplace is increasing. The presence of a marketplace in Indonesia is a means to increase product sales online. This study aims to determine and analyze the influence of social media influencers and testimonials simultaneously on the interest in buying Erigo products on the marketplace in Indonesia, knowing and recognizing the partial influence of Social Media Influencers on buying interest in Erigo products on the marketplace in Indonesia, knowing and analyzing the influence of testimonials in Indonesia. partial to the interest in buying erigo products on the marketplace in Indonesia. The type of research used in this research is quantitative research. The population and sample in this study are active users of social media and at the same time Instagram followers of Erigo Store with a total of 2.5 million followers aged between 17-40 years. The sampling technique used in this research is purposive sampling. The types of data used in this study include primary data. The data collection method used in this study was a questionnaire. The analytical technique used was multiple linear regression analysis. The results of this study indicate that simultaneously social media influencer variables and testimonials have a significant effect on buying interest in Erigo products. The results of hypothesis testing show that partially the two independent variables, both social media influencers and testimonial variables, have a positive and significant effect on buying interest in Erigo products. the regression coefficient of the Social Media Influencer variable is 0.300 and the Testimonial variable is 0.346. Keywords: Marketplace, Social Media Influencers, Testimonials, Buying Interest